2019
DOI: 10.1002/tea.21512
|View full text |Cite
|
Sign up to set email alerts
|

An international collaborative investigation of beginning seventh grade students' understandings of scientific inquiry: Establishing a baseline

Abstract: Although understandings of scientific inquiry (as opposed to conducting inquiry) are included in science education reform documents around the world, little is known about what students have learned about inquiry during their elementary school years. This is partially due to the lack of any assessment instrument to measure understandings about scientific inquiry. However, a valid and reliable assessment has recently been developed and published, Views About Scientific Inquiry (VASI; Lederman et al. [2014], Jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
71
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 28 publications
3
71
1
11
Order By: Relevance
“…In line with these definitions, science literacy is one of the most important concepts of 21 st century science education and its most integral components are "subject-matter knowledge", "nature of science views" and "scientific inquiry" (Lederman, 2009). Scientific inquiry (SI) basically refers to the combination of having science process skills, understandings about how scientists produce scientific knowledge, having subject matter knowledge, creativity and critical thinking in problem solutions (Lederman et al 2019). The importance of gradual development of scientific inquiry skills and understandings of students is emphasized in both international and national reform documents as one of the important objectives of science education (Benchmarks for Science Literacy, AAAS, 1993; A Framework for K-12 Science Education: Practices, Crosscutting Concepts, and Core Ideas, National Research Council [NRC], 2011; Ministry of National Education, 2018).…”
Section: Extended Abstract Introductionmentioning
confidence: 99%
“…In line with these definitions, science literacy is one of the most important concepts of 21 st century science education and its most integral components are "subject-matter knowledge", "nature of science views" and "scientific inquiry" (Lederman, 2009). Scientific inquiry (SI) basically refers to the combination of having science process skills, understandings about how scientists produce scientific knowledge, having subject matter knowledge, creativity and critical thinking in problem solutions (Lederman et al 2019). The importance of gradual development of scientific inquiry skills and understandings of students is emphasized in both international and national reform documents as one of the important objectives of science education (Benchmarks for Science Literacy, AAAS, 1993; A Framework for K-12 Science Education: Practices, Crosscutting Concepts, and Core Ideas, National Research Council [NRC], 2011; Ministry of National Education, 2018).…”
Section: Extended Abstract Introductionmentioning
confidence: 99%
“…practices that can contribute to promote literacy in the citizenship and the students became autonomous and independent thinkers that are able of answering relevant issues (ROBERTS, 2008) -involves different aspects and practices, and two of them are doing inquiry and knowing inquiry. Even though they are intrinsically related it is often assumed that students who do inquiry will necessarily develop understandings about inquiry (LEDERMAN et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, Lederman et al (2019) explain that there is an intuitive misconception that knowing about SI is linked with the doing of SI specially because part of the researches emphasized the doing of inquiry, which oftentimes is assumed to imply an understanding of inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have found that neither teachers nor students typically hold informed views of NOS (e.g. Lederman, Lederman, Bartels & Jimenez, 2019;Michel & Neumann, 2017;Dogan & Abd-El-Khalick, 2008, Kang, Scharmann & Noh, 2005Khishfe & Abd-El-Khalick, 2002).…”
Section: Introductionmentioning
confidence: 99%